The Rule Of Law Approach To Regulating Electricity Supply In Nigeria - Amadi, Sam (Journal of Sustainable Development Law and Policy, 2025)
With the transfer of government shares in 17 electricity generation and distribution companies in November 2013, Nigeria crossed the Rubicon in the privatization process. This process began in earnest in 2003 with the liberalization of the telecom sector as part of a strategic reform to improve efficiency in these utility sectors. So far, privatization has not improved the quality of service in these sectors. The problem has been traced to the failure of regulation. The major problem is that the regulatory regime had not matured before privatization. This immaturity manifests mostly in the failure to protect consumer interests. This article reviews regulatory deficits post-privatization. It assesses potential conflict between principles of market orthodoxy and those of constitutional governance and argues for a rule-of-law approach to regulation post-privatization that is focused on blending of promotion of market efficiency and protection of fundamental rights.